2015
DOI: 10.5194/se-6-1185-2015
|View full text |Cite
|
Sign up to set email alerts
|

MODIS normalized difference vegetation index (NDVI) and vegetation phenology dynamics in the Inner Mongolia grassland

Abstract: Abstract. The Inner Mongolia grassland, one of the most important grazing regions in China, has long been threatened by land degradation and desertification, mainly due to overgrazing. To understand vegetation responses over the last decade, this study evaluated trends in vegetation cover and phenology dynamics in the Inner Mongolia grassland by applying a normalized difference vegetation index (NDVI) time series obtained by the Terra Moderate Resolution Imaging Spectroradiometer (MODIS) during 2002-2014. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 52 publications
3
81
2
3
Order By: Relevance
“…However, by comparing the multi-year mean SOS/EOS of 2000-2004 and that of 2011-2015, we still found a significant advance of SOS in typical steppe and desert steppe, and a significant advance of EOS in desert steppe, which have also been identified by other studies with different data and methods [62,74]. SOS experienced a larger shift than EOS.…”
Section: What Factors Contributed To Sos/eos Trendssupporting
confidence: 79%
“…However, by comparing the multi-year mean SOS/EOS of 2000-2004 and that of 2011-2015, we still found a significant advance of SOS in typical steppe and desert steppe, and a significant advance of EOS in desert steppe, which have also been identified by other studies with different data and methods [62,74]. SOS experienced a larger shift than EOS.…”
Section: What Factors Contributed To Sos/eos Trendssupporting
confidence: 79%
“…Other studies also confirm that the LST and NDVI changes are due to changes of the vegetation cover and residential areas. Studies by Gong et al (2015) and Valor and Caselles (1996) showed that NDVI and LST values show trends in vegetation cover and phenology changes. A study by Sandra et al (2015) showed that land degradation and regeneration areas can be investigated using NDVI satellite data.…”
Section: Discussionmentioning
confidence: 99%
“…The Landsat Thematic Mapper (TM) and ETM+ (Enhanced Thematic Mapper Plus) sensor images can be used to study relationship between surface temperature and land use types using thermal quantitative indicators (Weng, 2003;Streutker, 2003). Land surface temperature can be retrieved using data from NOAA-11 (National Oceanic and Atmospheric Administration) AVHRR (Advanced Very High Resolution Radiometer) channels 4 and 5 by emissivity calculation (France and Cracknell, 1994).…”
Section: S Zareie Et Al: Using Landsat Thematic Mapper (Tm) Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 368 NDVI data were first clipped and subsequently re-projected to an Albers equal-area projection by standard output projection parameters with the WGS84 datum using the MODIS re-projection Tool (MRT) downloaded from the National Aeronautics and Space Administration (NASA) website. The TIMESAT software was used to remove the noise in NDVI time series datasets by applying a Savitzky-Golay filter [27] which provided a simplified least-squares-fit convolution for smoothing and computing derivatives of a set of consecutive values [28]. Finally, the vegetation growing season (i.e., between April and October) was divided into spring (April and May), summer (between June and August), and autumn (September and October) [29].…”
Section: Data Sourcesmentioning
confidence: 99%